"Mdhara Vachauya" (The Old Man Is Coming) and "Kutonga Kwaro" (His/Her Style of Governance): Analysing Jah Prayzah's Music in Zimbabwe's Tumultuous Political Context. Issue 1 (2nd January 2020) - Chitando, Ezra; Mlambo, Obert B.
Abstract: Music has never been politically neutral; rather, it is composed and performed in definite historical, social, political and economic contexts. Furthermore, musical lyrics often carry open or hidden political messages. The interpretation of musical texts has thus often generated contestation in different contexts. This article examines the appropriation and contested interpretation of two songs by one artist, Jah Prayzah (the stage name of Mukudzei Mukombe), in Zimbabwe during the last years of the late President Robert Mugabe's rule. It analyses how these two songs were utilised in political struggles by different players on the Zimbabwean political scene. The article argues that the malleability of songs enabled various political groups to adopt Jah Prayzah's song " Mdhara Vachauya " (The old man is coming!) released in 2016 to express their hopes and aspirations. Similarly, his song " Kutonga Kwaro " (His/her style of governance) was embraced by one faction in the Zimbabwe African National Union–Patriotic Front (ZANU–PF) to call for a change of guard. When Emmerson Mnangagwa, Mugabe's deputy, assumed power on 24 November 2017, the theme song was " Kutonga Kwaro ", newly released in the same year. Its ascendancy, like his own, had been severely contested. However, musical texts are not entirely divorced from the identity of the artist. Thus, Jah Prayzah's personality and self-presentation are also analysed in the article. The central argument is that the artist's self-packaging, perceived political loyalties and association had a distinct impact on the reception of his music.